2009
DOI: 10.1111/j.1525-1446.2009.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

The San Francisco Collaborative: An Evaluation of a Partnership Between Three Schools of Nursing and a Public Health Department

Abstract: Many factors are contributing to a decline in the number of nurses who opt to choose public health nursing as a career option. One factor is the lack of preceptors in public health, which has led to the placement of nursing students in nontraditional clinical settings. Thus, many nursing students are not exposed to public health nursing while still in school. Graduating students may not have a clear idea of what a public health nurse is or does. The purpose of the study was to describe a collaborative project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Ongoing communication for clinical teaching‐learning activities from planning through implementation and evaluation is essential (Blum, ; Keller et al., ; Landry et al., ). Pilot partners agreed that face‐to‐face communication is necessary at the beginning of each individual partnership and found that phone and email communications were effective once the partners have formed a working relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing communication for clinical teaching‐learning activities from planning through implementation and evaluation is essential (Blum, ; Keller et al., ; Landry et al., ). Pilot partners agreed that face‐to‐face communication is necessary at the beginning of each individual partnership and found that phone and email communications were effective once the partners have formed a working relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The project findings led to the development of a Partnership Engagement Conceptual Model that was affirmed by HSC members. The PEM is based on project results (Figure 1) and supporting evidence from the literature Landry et al, 2009;Moon, Henry, Connelly, & Kirsch, 2005;Zahner & Gredig, 2005a, 2005b. The PEM is a novel synthesis of the attributes that support the development of a conceptual model of partnership engagement.…”
Section: Development Of the Partnership Engagement Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…Although not raised by participants, current literature is rife with concerns regarding the lack of recognition toward community engagement activities during tenure and promotion reviews, consequently discouraging the participation of developing faculty struggling to find time for this form of commitment (Feenstra et al, 2006;Huang, 2002;Klein et al, 2011;Landry et al, 2009;Marrero et al, 2013; Mooney-Melvin, 2014; E. P. Smith, Wise, et al, 2014;Sorensen & Lawson, 2011). Community members themselves may struggle to find time-their commitment to community initiatives is often unpaid, taking them away from either family or paid work (Dempsey, 2010;Feenstra et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The principles of service learning and benefits to students in such practice placements have long been recognized by professional faculties such as nursing and medicine (Carney et al, 2011;Dulmus & Cristalli, 2012;Feenstra, Gordon, Hansen, & Zandee, 2006;Landry, Lee, & Greenwald, 2009;Siegrist, 2004;K. M. Smith, Else, & Crookes, 2014;Sowan et al, 2004).…”
mentioning
confidence: 99%